PENGARUH KINERJA KEUANGAN TERHADAP RETURN SAHAM PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDOENSIA PERIODE 2007 – 2012 - B11110001, DELTA FENISA (Jurnal Manajemen Update, 2015)
The purpose of this research is to know about the effect of work finances to return good share with partial or simultaneous to company subsector food and drink that enrolled in stock exchange of indonesia in 2007-2012. Population in this research the company sub-sector food and drink that enrolled in stock exchange of indonesia 2007-2012. Sample was thoroughed as much as ten company with puposive sampling. Variable was thoroughed such as Earning Per Share (EPS), Price Earning Ratio (PER), Debt to Equity Ratio (DER) and Return On Equity (ROE) as free variable and return share with significant grade as fasten variable. Data is gotten through data of secondary from BEI and was analyzed use double regression. Base on result of testing hypothesis with Partially point out that variable of Earning Per Share (EPS) is not influence in significant retrun share with significant grade as big as 0,409 > 0,05, while variable Price Earning Ratio (PER), Debt to Equity Ratio (DER), and Return on Equity (ROE) influence significant to Return share with significant grade as big as 0,000 < 0,05.